1962
DOI: 10.1172/jci104464
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Human Placenta in the Transfer and Metabolism of Insulin*

Abstract: Since 1911 the problem of placental permeability to insulin has been studied sporadically. Carlson, Drennan, Orr and Jones (1, 2) observed that pregnant dogs failed to develop glycosuria after pancreatectomy and concluded that the fetus protected the mother against diabetes, presumably by diaplacental movement of some substance. Other investigators (3, 4), however, were unable to confirm these early studies. Results of work with goats (5), rabbits (6, 7) and mice (8) were variable and suggest that species diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

1962
1962
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 21 publications
4
33
0
2
Order By: Relevance
“…We found that modest hyperglycemia in a type 2 diabetic embryopathy model had lower birth defect incidence than that of type 1 diabetic embryopathy, which has a high degree of hyperglycemia (52). In contrast, insulin may have minimal roles in embryonic development because maternal insulin does not cross the human placenta (1,4,13). Thus, our findings in type 1 diabetes may be extrapolated to conditions of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…We found that modest hyperglycemia in a type 2 diabetic embryopathy model had lower birth defect incidence than that of type 1 diabetic embryopathy, which has a high degree of hyperglycemia (52). In contrast, insulin may have minimal roles in embryonic development because maternal insulin does not cross the human placenta (1,4,13). Thus, our findings in type 1 diabetes may be extrapolated to conditions of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…Insulin was recognised as a teratogen in chicken embryo in 1945 [27]. In the absence of specific antibodies [28], insulin is generally considered not to cross the human placenta [29] but studies do not adequately address early pregnancy. In mammals, moreover, we know that insulin is present in the maternal reproductive tract [30] and that receptors for insulin are present in the embryo as early as the morula stage [30].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Buse et al. (18), Wolf et al (19), and Spellacy et al (20) also indicate that the placenta represents a substantial barrier to the transport of insulin in humans. On the other hand, the possibility that the placenta may not be completely impermeable to insulin in the rat (21) as well as in other species (22)(23)(24) has been suggested by other investigators.…”
Section: Methodsmentioning
confidence: 93%